Perancangan Media Informasi Buku Ilustrasi Cerita Rakyat Tapa Malenggang - Fahimul Fuad; Harissman Harissman; Ary Leo Bermana; Rias Wita Suryani (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This design is entitled "Design of Information Media for Illustrated Books of Tapa Malenggang Folk Tales" such as learning media, to be an alternative solution to increase the expansion of information about Batanghari culture, namely the Tapa Malenggang Folk Tales through innovative information media. The solution is presented in the form of an illustrated book about the Tapa Malenggang Folk Tales using dynamic and colorful illustrations. This design method uses 5w + 1H analysis. While the design process includes interviews, field observations, library data, direct questionnaires to schools, and documentation. The process of creating works through several structured stages, namely brainstorming, sketches, storylines, color studies, typography studies and storyboards. Illustrated books are informative media that can be well captured by children's sense of sight. Supporting media for the design include e-books, posters, x-banners, stickers, pins, t-shirts, and key chains.